Evaluation of the antidiabetic and antinephritic effects of Pueraria tuberosa and Pterocarpus santalinus extracts co-encapsulated in nanostructured lipid carriers in streptozotocin-induced mouse model - Gyamcho Tshering Bhutia; Asit Kumar De; Manas Bhowmik; Pavia Bera; Tanmoy Bera (Phytomedicine Plus)
Background: Diabetic nephropathy (DN) causes significant morbidity and mortality, leading to substantial psycho-economic costs. New strategies and medications are needed to manage DN more effectively. Purpose: The antidiabetic and antinephritic properties of Pueraria tuberosa and Pterocarpus santalinus have been demonstrated in previous studies. However, poor oral bioavailability has limited their clinical application. A nanostructured lipid carrier (NLC) formulation was created and tested to address this problem. The promising experimental results suggest that this formulation holds potential for further clinical exploration. Study design: The in vivo study evaluated the therapeutic potential of NLCs loaded with hydroalcoholic extracts of P. tuberosa tubers (PTE) and P. santalinus heartwood (PSE) in managing DN over eight weeks in streptozotocin (STZ)-induced diabetic mice. Methods: The protective effects of PTE and PSE were evaluated in mice at a dose of 80 mg/kg body weight. Two weeks after STZ treatment, animals with blood sugar levels above 250 mg/dL were identified as diabetic and showed signs of nephritis. In these diabetic mice, PTE-NLC and PSE-NLC, individually and in their combined form (PTE+PSE)-NLC, were assessed for their hypoglycemic and nephroprotective effects. Animals were sacrificed for histopathological and biochemical analysis after eight weeks of therapy. Nanoparticles were characterized by their morphology, zeta potential, drug loading capacity, particle size, and release profile. Results: In STZ-induced diabetic mice, treatment with (PTE+PSE)-NLC significantly improved pancreas and kidney health. It restored the kidney hypertrophy index, stabilized biochemical parameters, enhanced histopathological outcomes, and increased beta-cell count. Additionally, (PTE+PSE)-NLC led to a 30.53-fold more significant reduction in blood glucose levels than free (PTE+PSE) extracts. Conclusion: Our findings highlight the potential of the NLC formulation of P. tuberosa and P. santalinus extracts in treating diabetic nephropathy. The bioactive compounds in these extracts play a crucial role in their antidiabetic and antinephritic effects, marking significant progress in the field.